Conexão eleitoral e comportamento parlamentar : um estudo a partir da Assembleia Legislativa do Espírito Santo entre 1999 e 2010 - Simões, Jessica Kamille Cruz (2018)
The general objective of this work was study the parliamentary behavior through the legislactive production of the assemblymen of the Assembleia Legislativa do Estado do Espírito Santo, between the years of 1999 e 2010, that is the 14ª, 15ª e 16ª legislatures, and to check if this behavior can be understood using as a key of explanation the electoral conection logic. We mobilized this concept developed by David Mayhew, according to which the assemblymen use estrategically the institucional resources that are avaiable during their mandate with the aim of re-electing. According to the electoral conection logic, the assemblyman search to benefit his electorate by distributing resources as a way to garante his electoral success. We studied the legislative production from two types of proposition, the law projects and the indications. From the analysis of their abstract, we characterized the legislative production profile in two aspectss: their theme and their level of scope. The hypothesis was that against a constitucional background of limitation to the production of distributive law projects, the criation and use of the indications were conditioned to the need of propose regionally circumscribed benefits to their electorade. We verified that the law projects profile prodution was diferente from the indications profile production, being that these ones wer more used to propose distributive benefits. We also defined from the electoral results the voting geographical profile of the assemblyman elected in the studied period from two aspects: if the assemblyman had a concentrated voting in a region of the state or not; and if the most of the voting came from the metropolitan region or not. The objective was to investigated if the incentives coming from the electoral arena reflect in the legislative production profile. The hypothesis was that different geographic voting profile generate different legislative profile production. We concluded that in the studied period there wasn’t a strong relation between the legislative production profile and the voting geographical profile, so that it wasn’t possible to affirm that the electoral connection logic works as a key of explanation for this aspect of the parliamentary behavior in the studied temporal and spatial framework.